Labor supply within the firm - Michele Battisti; Ryan Michaels; Choonsung Park (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
Estimates of labor supply elasticities can be sensitive to the source of identifying variation. Thispaper's model of production complementarities helps to interpret conflicting evidence.Complementarities attenuate working time adjustments to idiosyncratic, or individual-specific,variation in work incentives. Complementarities do not restrict, however, responses to firm-wideshocks; the latter is mediated by preference parameters. Estimating the model using matchedfirm-worker data, the paper disentangles production from preference parameters. The Frischelasticity along the intensive margin is found to be around 0.5. A quasi-experimental approach,using idiosyncratic variation in work incentives, would find an elasticity less than half this.
Keywords: J22; J23; J31; 330; Intensive margin; production complementarities; bargaining; employee-employer data